Peran KOPDIT CU Mandiri dalam Pemberdayaan Ekonomi Masyarakat Pematang Siantar - Putri Khairunnisa; Octa Palentina Saragih; Dian G. Purba; Hartati Rodearna Sitio; Demak A. Purba; Widyadamanik, Widyadamanik; Jun Kifran Riando Manik; Dimas S. A. Nasution (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Credit Union (CU) Mandiri is one of the cooperative-based microfinance institutions that plays an important role in improving the economic welfare of the community in Pematang Siantar. This study aims to analyze the contribution of CU Mandiri in empowering its members through savings and loan programs, financial literacy training, and micro-business development. The method used in this study is a descriptive qualitative approach, with data collection techniques through interviews, observations, and documentation studies. The results of the study show that CU Mandiri not only provides affordable financing access for low-income communities, but also increases the awareness and ability of its members to manage their finances independently. Through cooperative principles such as solidarity and active participation of members, CU Mandiri has succeeded in creating an environment that supports local economic growth. However, challenges such as low financial literacy and limited capital are still obstacles that need to be addressed systematically.